Novel Co/UiO-66 metal organic framework catalyst for oxygen reduction reaction in microbial fuel cells - Chen, Zhenxin; Wu, Qikai; Zhang, Hongguo (E3S web of conferences, 2021)
To improve the power generation of microbial fuel cell (MFC), the cathode is modified to increase its oxygen reduction reaction (ORR) activity by using Co/UiO-66, which derived from pyrolyzing the mixture of Co(NO3) 2 as the metal precursor incorporated with NH2-UiO-66. It was found that Co/UiO-66 (MOF-900) has been developed as a high-performance electrocatalyst for ORR at a pyrolysis temperature of 900 °C. Therefore, Co/UiO-66 should be a promising oxygen reduction catalyst for application in MFCs. This study provides technical and theoretical validation for the MFC performance improvement by ORR active MOF-derived catalysts modified cathodes.